Characteristic of cow milk dadih using starter of probiotic of lactic acid bacteria - Usmiati, Sri; Broto, W.; Setiyanto, H. (Indonesian Animal Sciences Society, 2011)
Dadih is an original dairy product from West Sumatera processed traditionally. It is a spontaneous fermentation of buffalo milk at room temperature for 48 hours in a bamboo tube, has no standard of processing and quality. Dadih is potentially to be develop into probiotic products (functional food) that can be enjoyed by the public widely. Development of cows milk dadih is necessary since buffalo milk is available only in certain area. Product and characteristic information of cow milk dadih using probiotic of lactic acid bacteria starter has not been known. The research objective was to determine the characteristics of cow milk dadih that used starter of probiotic lactic acid bacteria during storage at room temperature (27oC) and cold temperature (4oC). The study was designed using a factorial randomized block design pattern 12x3 at room temperature and 12X4 at cold temperatures, with the number of repeatation of 3 times. Treatment consisted of: (i) starter formula (A) using a single bacterium or a combination of Lactobacillus acidophilus, Lactobacillus casei and Bifidobacterium longum, and (ii) storage time (B). Observed parameters included pH value, titrable acidity, the total plate count, and in-vitro probiotic testing (bacterial resistance to bile salts and low pH) of cow milk dadih. The results showed that L. acidophilus early exponential phase was at the hour 3rd, L. casei at the hour 4th and B. longum on the 3rd of which is used as the optimum time of mixing two or more bacteria in the manufacture of cow milk dadih. The volume of starter used was 3% with time fermentation of 48 hours at room temperature (27-30oC). Cow milk dadih that was stored for 7 days at room temperature (27-30oC) and for 21 days at cold temperatures (4-10oC) was able to maintain viability of bacteria to bile salts and low pH at 1010-1012 cfu/ml with percentage resistance varied. The cow milk dadih using a combination starter of B. longum with other probiotics on the composition of 1:1 had a resistance to bile salts which were relatively constant after the dadih was kept for 21 days at cold temperature. Cow milk dadih with a starter of probiotic bacteria still qualify as a probiotic product with good quality that storaged up to 4 days at room temperature and 21 days in cold temperatures. Key Words:Â Dadih, Probiotic, Lactobacillus Acidophilus, Lactobacillus Casei, Bifidobacterium Longum